Review of guidelines for children's vision screenings. (25th February 2013) - Hopkins, Shelley; Sampson, Geoff P; Hendicott, Peter; Wood, Joanne M
Abstract : The aim of children's vision screenings is to detect visual problems that are common in this age category through valid and reliable tests. Nevertheless, the cost effectiveness of paediatric vision screenings, the nature of the tests included in the screening batteries and the ideal screening age has been the cause of much debate in Australia and worldwide. Therefore, the purpose of this review is to report on the current practice of children's vision screenings in Australia and other countries, as well as to evaluate the evidence for and against the provision of such screenings. This was undertaken through a detailed investigation of peer‐reviewed publications on this topic. The current review demonstrates that there is no agreed vision screening protocol for children in Australia. This appears to be a result of the lack of strong evidence supporting the benefit of such screenings. While amblyopia, strabismus and, to a lesser extent refractive error, are targeted by many screening programs during pre‐school and at school entry, there is less agreement regarding the value of screening for other visual conditions, such as binocular vision disorders, ocular health problems and refractive errors that are less likely to reduce distance visual acuity. In addition, in Australia, little agreement exists in the frequency and coverage of screening programs between states and territories and the screening programs that are offered are ad hoc and poorly documented. Australian children stand to benefit from improved cohesion and communication between jurisdictions and health professionals to enable an equitable provision of validated vision screening services that have the best chance of early detection and intervention for a range of paediatric visual problems.